Proceeding to a postgraduate research degree: some tips - Hasan , Md. Mahmudul (English Department Alumni Society, University of Dhaka, 2007)
Bangladeshi students generally think about embarking upon a structured, academic research project after completing their first degrees, honours and masters. Students with laudable academic credentials wish to do so in a foreign country, preferably in the West. However, when a Bangladeshi postgraduate research student goes to a western university to undertake their research career, s/he find themselves in an unenviable situation in terms of their knowledge about the essentials of research process and of their perceptions of research skills. I do not blame the students for this particular indefensible, worrying phenomenon. The entire education system of Bangladesh, especially the university education system, has failed to nurture or develop the research acumen of students satisfactorily. Nor does it adequately educate them in successfully conducting an academic research project on a reasonable scale. Some skills that students were meant to learn at collegiate level remain foreign to them even after obtaining a masters degree. This applies to both 'good' and 'mediocre' students. Obviously, with such an academic background, when a student goes to, for example, a British university with the ambition to undertake a postgraduate research degree, s/he finds it difficult to adapt themselves to a superior educational culture that emphasises, and draws most heavily upon, research-based studies.